The Relationship of Musician to Political Power in the Process of Modernization: The Eulogies Composed for Selim III and Mahmud II - (:unkn) unknown (ISTANBUL UNIV, FAC LETTERS,DEPT SOCIOLOGY, 2017)
The patronage system, which can be defined as support of an artist by a prosperous patron, has been one of the most important factors in ensuring the continuity of artistic production up to the modern market system. In the context of this relationship, artists hav e formed their artistic works through patron's pleasures and wishes in return for the support they receive. This study examines the relationship of sultans, who were major patrons of the Ottoman musical tradition, with the musicians around them through the composed eulogies (medhiye). It is limited to the reigns of Selim III and Mahmud II, who were also musicians. In spite of the prevalence in Ottoman poetry, examples of eulogies are limited in Ottoman music, with 35 composed eulogies having been found for this period. These musical works have been analyzed according to composer, mode (makam), rhythm (usul), form, and dedication. Another dimension in this study is an evaluation of these eulogies' lyrics. After focusing on each set of lyrics, the texts have been examined according to the themes set out under categories such as prayer, praise, and greeting. Thus the subjects that are significant in the eulogies have been identified.
Keywords: Eulogy; Ottoman music; Patronage; Relationship of musician to political influence; Selim III; Mahmud II